Atypical Chronic Central Serous Chorioretinopathy Mimicking Vogt-Koyanagi-Harada Disease: Full Therapeutic Response to Half-Fluence Photodynamic Therapy - Özge Yanık; Figen Batıoğlu; Nilüfer Yalçındağ; Sibel Demirel; Emin Özmert (Türk Oftalmoloji Dergisi)

(untitled)
The aim of this case report is to describe a case of atypical central serous chorioretinopathy (CSCR) definitively diagnosed after 8 years. A 44-year-old woman presented with reduced visual acuity in her left eye. Her visual acuity was light perception with projection in the right eye and 0.15 in the left. She described a similar decline in vision in her right eye 8 years ago. At that time, she had exudative retinal detachment and was treated with systemic immunosuppressive therapy for a presumed diagnosis of Vogt-Koyanagi-Harada disease. Despite resolution of the exudative retinal detachment, macular scarring developed. Eight years later, she developed inferior exudative retinal detachment in the left eye. A diagnosis of atypical CSCR was made with the help of multimodal imaging and her left eye was successfully treated with eplerenone and half-fluence photodynamic therapy (hf-PDT). In conclusion, early diagnosis and treatment of atypical CSCR may prevent subretinal fibrosis formation and permanent vision loss. Hf-PDT and eplerenone are successful treatment options for atypical CSCR.